The effects of authentic materials on students’ writing of procedural text - Zulida Arifa (Journal on English as a Foreign Language, 2011)
The objective of the study was to find whether there was a significant difference between the students taught using authentic materials and the students taught using non-authentic materials on the students’ writing score. The quasi-experimental design was applied in this study. The population was all the tenth year students at MAN Model Palangka Raya. The samples were determined using purposive sampling. The samples were XA as the experiment group and XB as the control group. The collected data were obtained from test and documentation. The main data were analyzed using ttest formula and SPSS 17.0. The results showed that the mean of pre-test score in experiment group was 59.76 and the mean of post-test score was 72.9. The value difference of both means was 13.14. The mean of pre-test score in control group was 53.8 and the mean of post-test score was 58. The value difference of both means was 4.2. It means that teaching writing procedural text using authentic materials was more effective than teaching writing procedural text using non-authentic materials because the authentic materials taught was appropriate with the level of students’ ability in this study.